2022
DOI: 10.29244/j.agromet.36.2.70-78
|View full text |Cite
|
Sign up to set email alerts
|

Baseflow Index Analysis for Bengawan Solo River, Indonesia

Abstract: Hydrological investigation for major Java rivers remains research challenge todays, particularly in identification of runoff characteristics situated in monsoonal climate. This study aims to investigate the value of baseflow index for Bengawan Solo river. We employed daily streamflow data for period 1980-2010 to derive baseflow index (BFI) based on the smoothed minima. We utilized different approaches comprising the non-overlapping 3 days (BFI3), 5 days (BFI5), and 7 days (BFI7) of streamflow to compute the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The calculated BFI values in this study range from 0.60 to 0.68, which is consistent with studies conducted in Brazil [71] and Indonesia [72] in similar environments. However, other regions in Indonesia have shown smaller BFI values (ranging from 0.49 to 0.56) compared to Ankavia [73]. In contrast, higher BFI values were reported for watersheds in Thailand [74] and Malaysia [75].…”
Section: General Hydrological Characteristicsmentioning
confidence: 82%
“…The calculated BFI values in this study range from 0.60 to 0.68, which is consistent with studies conducted in Brazil [71] and Indonesia [72] in similar environments. However, other regions in Indonesia have shown smaller BFI values (ranging from 0.49 to 0.56) compared to Ankavia [73]. In contrast, higher BFI values were reported for watersheds in Thailand [74] and Malaysia [75].…”
Section: General Hydrological Characteristicsmentioning
confidence: 82%
“…Bengawan Solo watershed faces several environmental challenges such as flood, drought, critical land, water pollution, erosion, sedimentation, and other social issues (Hannum et al, 2020;Taufik and Annisa, 2022). Several studies have explored changes in rainfall patterns in the Bengawan Solo watershed, including Auliyani and Wahyuningrum (2020), which reported an increased trend in rainfall for the upstream Bengawan Solo, and Trinugroho et al, (2022), which found the coastal regions of the Bengawan Solo Sub-Watershed experience a downward trend, which means that coastal regions will become drier than mountainous regions in the future.…”
Section: Introductionmentioning
confidence: 99%